Effectiveness, safety and comfort of StatLock securement for peripherally‐inserted central catheters: A systematic review and meta‐analysis. (21st July 2017) - Luo, Xianwu; Guo, Yi; Yu, Huidan; Li, Sheng; Yin, Xiaohong
Abstract: In this systematic review and meta‐analysis, we evaluated the effectiveness, safety and comfort of StatLock for the securement of peripherally‐inserted central catheters. PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure, WanFang Database, and China Science and Technology Journal Database were searched. Randomized, controlled trials comparing StatLock with tape or suture on the performance of securing peripherally‐inserted central catheters were selected. Meta‐analysis was performed using Review Manager 5.3 software. Thirteen randomized, controlled trials involving 1970 patients were included. Our results showed that StatLock reduced the incidence of catheter dislodgement and unplanned removal. Moreover, patients in the StatLock group had lower incidence of skin ulceration, phlebitis, catheter‐related bloodstream infection, and cellulitis, and felt more comfortable compared with those in the control group. Current evidence suggests that the StatLock securement device offer advantages over tape and suture in preventing catheter‐related complications and improving patient comfort. However, as considerable heterogeneity was found among the included studies, and the quality of evidence for main outcomes was relatively low, the results should be viewed with caution.